Analgesic Effect of Interscalene Block Using Low-Dose Bupivacaine for Outpatient Arthroscopic Shoulder Surgery. Issue 5 (September 1998) - Al-Kaisy, A.; McGuire, G.; Chan, V. W.S.; Bruin, G.; Peng, P.; Miniaci, A.; Perlas, A.
Abstract : Background and Objectives: Although interscalene brachial plexus block (ISBPB) is often used to provide anesthesia for arthroscopic shoulder surgery, its selective analgesic effect, provided by low-dose local anesthetic, has not been studied. We hypothesized that ISBPB using a low volume and low concentration of bupivacaine can provide effective postoperative analgesia for shoulder surgery without producing significant sensory or motor block elsewhere. Methods: In this double-blind study, 30 outpatients scheduled to undergo shoulder arthroscopy were randomly assigned to receive either an ISBPB with 10 mL 0.125% bupivacaine with epinephrine 1:400, 000 (n = 15) or 10 mL of normal saline (n = 15). The block was performed preoperative, prior to a standardized general anesthetic. Postoperative pain scores, morphine and oral analgesic consumption, recovery profile, and patient satisfaction were recorded. Results: In the ISBPB group, verbal analog pain scores within 120 minutes after surgery were lower, morphine consumption in the postanesthesia care unit was significantly lower (2.7 ± 2.6 mg vs 9.5 ± 5.2 mg), the time to postoperative administration of the first systemic or oral analgesic was significantly longer (141 ± 182 minutes vs 13 ± 10 minutes), the degree of motor and sensory block 120 minutes after surgery was minimal, time to reach hospital discharge criteria was earlier, and patient satisfaction with postoperative analgesia at 24-hour follow-up was greater. Thirty-three percent of the patients receiving ISBPB did not require any analgesic prior to hospital discharge. Conclusions: Interscalene brachial plexus block with low-dose bupivacaine is a useful and selective analgesic technique for outpatient shoulder arthroscopic surgery.